IMPORTANCIA DE LAS RELACIONES INTERDISCIPLINARIAS DE LA BIOLOGÍA EN LA CARRERA DE PSICOLOGÍA CLÍNICA: IMPORTANCE OF THE INTERDISCIPLINAR RELATIONSHIP OF BIOLOGY IN THE CAREER OF CLINIC PSYCHOLOGY - Suárez Hurtado, Ludwing Amalio; Acosta Luis, Dania; Suárez Reinoso, Keyla Yamali (Opuntia Brava, 2018)
En el Plan de Estudio de la carrera de Psicología Clínica se inserta la asignatura de Psicobiología humana y Psicoestadística, pues ofrecen valiosos conocimientos en el diagnóstico que harán los futuros psicólogos clínicos. Determinar la prevalencia de Entamoeba histolitica / E. dispar y otros protozoos intestinales por control coproparasitario en los estudiantes del Instituto Superior Pedagógico “Los Ríos”, para proponer medidas preventivas, es el interés esencial de este trabajo. Entre las vías utilizadas para lograr el objetivo, destacamos el estudio de casos e investigación participativa. El grupo de casos comprendió a los estudiantes que tiene la sección superior, realizándose el examen coproparasitario con el empleo de solución fisiológica y solución de yodo. El grupo encuestado abarcó a los estudiantes de los diferentes niveles. La información se recogió de las historias clínicas de cada estudiante y las respuestas al cuestionario aplicado al grupo de muestra. ABSTRACT The study of clinical psychology career is considered obvious to consider the subject of human psychobiology and Psychostatistics within the curriculum. It is a previous knowledge of relevance in the precise and accurate diagnosis to make clinical psychologists who are prepared in our career. Determine the prevalence of Entamoeba histolytica / E. dispar and other intestinal protozoa by control coproparasitism students to propose preventive measures, is essential for this work. Various ways have been used to achieve this. Among them we highlight as materials and methods the study of cases and participatory research. This study is part of the subject of human psychobiology, who relies on the Psychostatistics to establish the tabulation, processing and classification of information collected through the different techniques and procedures. The Group of cases included students who has the top, performing the examination coproparasitism using saline solution and iodine solution. The respondent group encompasses students of different levels. The information was collected from each enrolled student records and responses to the questionnaire applied to the sample group. KEY WORDS: intestinal protozoa, prevalence, control coproparasitism.